2014
DOI: 10.1177/1040638714534237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and virulence gene profiling of pathogenic Streptococcus agalactiae populations from tilapia (Oreochromis sp.) farms in Thailand

Abstract: Abstract. Streptococcus spp. were recovered from diseased tilapia in Thailand during 2009-2010 (n = 33), and were also continually collected from environmental samples (sediment and water) from tilapia farms for 9 months in 2011 (n = 25). The relative percent recovery of streptococci from environmental samples was 13-67%. All streptococcal isolates were identified as S. agalactiae (group B streptococci [GBS]) by a species-specific polymerase chain reaction. In molecular characterization assays, 4 genotypic cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 35 publications
2
69
0
3
Order By: Relevance
“…In theory, the floating cages culture system, where the fish are naturally exposed to various potential pathogens, is predictably infected by multiple (Ariel and Owens, 1997;McGrogan et al, 1998;Figueiredo et al, 2005;Olivares-Fuster et al, 2008;Dong et al, in press;Kayansamruaj et al, 2014a;Kayansamruaj et al, 2014b). In contrast, A. veronii, P. shigeloides and V. cholerae are not welldescribed fish pathogens and have been identified as foodborne pathogens that could present a serious issue to consumer health (Joseph et al, 1991;Nadirah et al, 2012;Chen et al, 2013;Chen et al, 2014;Nguyen et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In theory, the floating cages culture system, where the fish are naturally exposed to various potential pathogens, is predictably infected by multiple (Ariel and Owens, 1997;McGrogan et al, 1998;Figueiredo et al, 2005;Olivares-Fuster et al, 2008;Dong et al, in press;Kayansamruaj et al, 2014a;Kayansamruaj et al, 2014b). In contrast, A. veronii, P. shigeloides and V. cholerae are not welldescribed fish pathogens and have been identified as foodborne pathogens that could present a serious issue to consumer health (Joseph et al, 1991;Nadirah et al, 2012;Chen et al, 2013;Chen et al, 2014;Nguyen et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Hemolysis has been considered as an important virulent factor of S. agalactiae (Olivares-Fuster et al, 2008;Kayansamruaj et al, 2014b). Previous studies revealed that a high temperature ( A C C E P T E D M A N U S C R I P T A C C E P T E D M A N U S C R I P T A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…; Kayansamruaj et al . ); francisellosis caused by Francisella noatunensis subsp . orientalis (Soto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Virulence‐associated factors including those driving bacterial adhesion and colonization (Lmb, DltA, BibA, FbsA, FbsB and pili), bacterial invasion (HylE, CspA, and Gap), immune evasion (CylE, CpsA, ScpB and sialic acid) and toxicity (CylE, HylB and Cfb) can promote GBS entry into host cells and facilitate the intracellular survival and spread of GBS (Kayansamruaj, Pirarat, Katagiri, Hirono, & Rodkhum, ; Shabayek & Spellerberg, ; Udo, Boswihi, & Al‐Sweih, ; Zhang et al, ). Additionally, the capsule covers the outer layer of GBS strains, which is mainly composed of the capsular polysaccharide (CPS).…”
Section: Introductionmentioning
confidence: 99%